2021
DOI: 10.1002/jmv.27249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a SARS‐CoV‐2 antigen‐detecting rapid diagnostic test as a self‐test: Diagnostic performance and usability

Abstract: To control the spread of the coronavirus disease 2019 (COVID‐19) epidemics, it is necessary to have easy‐to‐use, reliable diagnostic tests available. The nasopharyngeal sampling method being often uncomfortable, nasal sampling could prove to be a viable alternative to the reference sampling method. We performed a multicentre, prospective validation study of the COVID‐VIRO® test, using a nasal swab sampling method, in a point‐of‐care setting. In addition, we performed a multicentre, prospective, and usability s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Although there is reduced sensitivity compared to using NP swabs in our evaluation, the NA swab offers several advantages. It is less invasive, which is more acceptable by people compared to NP swabs ( 26 , 27 ), and the ease of use facilitates volunteer training and self-testing at home or workplace ( 28 , 29 ). These factors, combined with rapid turnaround time, low cost, and ease of use afforded by Ag-RDTs ( 30 32 ), can help facilitate repeat testing over time and may compensate for reduced sensitivity ( 5 , 9 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is reduced sensitivity compared to using NP swabs in our evaluation, the NA swab offers several advantages. It is less invasive, which is more acceptable by people compared to NP swabs ( 26 , 27 ), and the ease of use facilitates volunteer training and self-testing at home or workplace ( 28 , 29 ). These factors, combined with rapid turnaround time, low cost, and ease of use afforded by Ag-RDTs ( 30 32 ), can help facilitate repeat testing over time and may compensate for reduced sensitivity ( 5 , 9 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This quite likely results from the on average low viral load in 1 study [49], and the asymptomatic study population in the other [175]. On the contrary, compared to the other studies unusual high sensitivity was found in studies where average viral load was high [45, 84, 144, 145] or participants were mainly within the first week of symptom onset [42, 54, 135].…”
Section: Discussionmentioning
confidence: 99%
“…6 and 94 reported positive and negative results respectively. 1 This study is appealing and we had a similar study performed in Hong Kong.…”
mentioning
confidence: 99%